R. K. Singh: The Poet Who Celebrates ’senses’ to attain ’Nirvana’ - Dr. Ram Kulesh Thakur (University of Chitral Journal of Linguistics and Literature, 2025)
This paper discusses a few of R.K.Singh’s characteristic poetic traits that make him stand apart from all his contemporary Indian poets writing in English. His poetry is an honest attempt to portray the contemporary world in its true hue and color; present an inside-out delineation of the modern man; and touch upon all the socalled ‘untouchable’ i.e., topics such as ‘Sex’, ‘Prostitution’, ‘Cultural Degradation’, ‘Stinking Politics’, ‘Religion’, etc. Reader finds Singh celebrating all his senses in his ‘unique’ attempt to attain the state of complete ‘Peace’ or ‘Calm’. His poetry serves as a medium for him to reach the state of ‘nirvana’. Reader finds Singh’s poetry as a prism that diffracts the worldly affairs into different spectrums, analyses each, and again sums it all into a single hue of liberation and peace with ‘detachment’ displaying the mark of a seasoned ‘yogi’. The paper aims to encourage other researchers and people in the academia to explore recent band of emerging Indian poets expressing themselves in English.